Secret mission to the Philippines the story of the "Spyron" and the American-Filipino guerrillas of World War II - Wise, William 1923- (New York Dutton, 2001)
Describes the unusual World War II command of Chick Parsons who, as leader of the American-Filipino guerrilla movement, lived behind enemy lines, never carried arms or fired a shot, and became one of America's most decorated heroes.
Originally published by E. P. Dutton, 1968.
Keywords: Parsons, Charles -- 1901- -- Juvenile literature; Parsons, Charles -- 1901-.; World War, 1939-1945 -- Underground movements -- Philippines -- Juvenile literature; World War, 1939-1945 -- Underground movements -- Philippines